Multikulturalisme sebagai identitas bangsa Indonesia: Peluang dan tantangan di era globalisasi - Nurochmah, Alfiah Fadina (Maliki Interdisciplinary Journal, 2026)
Multiculturalism is a social condition that reflects the diversity of ethnic groups, cultures, languages, and religions, which has become a distinctive identity of Indonesia. This study discusses multiculturalism as the national identity of Indonesia, as well as the opportunities and challenges that arise in the era of globalization. The aim of this study is to understand how diversity can become a strength in building national identity, while also examining the impact of globalization on local cultural values and social life. This study uses a literature review method by analyzing various scientific sources such as journals, articles, and data related to Indonesia’s socio-cultural conditions. The findings show that multiculturalism in Indonesia provides great opportunities to strengthen national unity, develop cultural creativity, and enhance more open social interaction among communities. In addition, globalization also creates opportunities for Indonesia to introduce its local culture to the international level. However, globalization also brings several challenges, such as the potential increase of social conflict, the weakening of local cultural values, and the emergence of intolerance among society. Therefore, it is important to strengthen Pancasila values, character education, and public awareness in maintaining harmony within diversity. In conclusion, multiculturalism is an important identity of the Indonesian nation that must be preserved and developed in balance with the influence of globalization.